Saggi su Plutarco e la sua fortuna - DESIDERI, Paolo (Firenze University Press, 2012)
The volume is a collection of 21 essays on the work of Plutarch and his fortune in the modern era, already published in classical philology and ancient history journals, or in collected volumes. The essays are grouped under topics (The Cultural Context, Politics, History, Plutarch and European Culture, Between Past and Future) and have a unified bibliography, with indexes of the ancient names and passages discussed.